2017
DOI: 10.7748/phc.2017.e1157
|View full text |Cite
|
Sign up to set email alerts
|

Positive Approaches to Care: a new look at dementia education

Abstract: This article provides an overview of relevant factors in dementia care. The number of people experiencing dementia is increasing and dementia is at the forefront of health policy. The evidence base for personcentred approaches and interventions in dementia is expanding and nurses are central to implementing these across care settings. This is a challenging time for dementia care and nursing has a major role in leading and developing these changes in practice. The article discusses the Positive Approaches to Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Moreover, at the content level, the competencies appeared heterogeneous and not eligible to prepare professionals to face the complexity of dementia care (Traynor et al, 2011). Similar scenarios emerge in other reports (Downs et al, 2009;Murphy, 2017;Pulsford et al, 2007). In the UK, Pulsford et al (2007) found that the topics concerning dementia were usually taught indirectly, incorporated within broader teaching content, encapsulated in short modules, or delivered through seminars.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Moreover, at the content level, the competencies appeared heterogeneous and not eligible to prepare professionals to face the complexity of dementia care (Traynor et al, 2011). Similar scenarios emerge in other reports (Downs et al, 2009;Murphy, 2017;Pulsford et al, 2007). In the UK, Pulsford et al (2007) found that the topics concerning dementia were usually taught indirectly, incorporated within broader teaching content, encapsulated in short modules, or delivered through seminars.…”
Section: Introductionmentioning
confidence: 73%
“…However, within the Second cycle of studies, masters of various natures are hosted: ISCED includes masters offered to full-time students alongside masters for working professionals and study programs that do not provide accreditations to spend in the labour market (UNESCO, 2012(UNESCO, , 2015. As observed elsewhere (Pulsford et al, 2007;Downs et al, 2009;Murphy, 2017;Hvalič-Touzery et al, 2018), skills on dementia care are very often provided in courses that organized outside the universities, i.e., CPD learning programs, once people already got a degree (Hvalič-Touzery et al, 2018). Such heterogeneity can confound students, academic officers, professionals and their agencies, the world of work, and the general audience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation